Empowering children : a multicultural humanistic approach - Kazanjian, Christopher J. (New York, NY : Routledge, 2021)
"This unique text bridges multiculturalism and humanistic psychology, demonstrating how these areas can be effectively integrated to provide a foundation for engaging youth in the global community. Through a detailed case study and phenomenological study results, this book offers an immersive framework for multicultural humanistic psychology that will be of value to researchers and professionals alike"--
OCLC-licensed vendor bibliographic record.
Keywords: Multiculturalism; Humanistic psychology; After-school programs; Child development; EDUCATION / Counseling / General; EDUCATION / Educational Psychology